ARTIFICIAL INTELLIGENCE IN THE BRAZILIAN JUDICIARY: PROCEDURAL EFFICIENCY AND GUARANTEES OF DUE PROCESS OF LAW (REMUNOM, 2026)
This article aims to examine the incorporation of artificial intelligence systems in the Brazilian Judiciary, highlighting the tension between efficiency gains and the preservation of due process guarantees. The research adopts a qualitative approach, with a deductive method, based on a literature review and documentary analysis of constitutional norms, infra-constitutional legislation, normative acts of the National Council of Justice, and specialized studies on technology and jurisdiction. Considering the digital transformation of justice, the legal limits of automation in the procedural flow are investigated, as well as the need for strict observance of constitutional precepts, such as transparency, adversarial proceedings, full defense, motivation of decisions, and qualified human supervision. It is argued that artificial intelligence can act as a tool to support administrative rationalization and procedural speed, without replacing the jurisdictional function exercised by the magistrate. Therefore, a model is advocated in which such technologies operate under effective institutional control, with clear criteria for auditability and accountability. It is concluded that the adoption of technological solutions in the judicial sphere is only legitimate when aligned with the protection of fundamental rights, the integrity of the process, and public accountability, ensuring that innovation does not compromise confidence in the justice system.